Co-relation of coagulation profile with glycemic index in patients with type 2 diabetes - Sushil Kumar; Soma Dey; Abhilasha Bankul; Bandana Kumari; Bankim Das; Goutham Giri (Journal of Family Medicine and Primary Care)
Background: Diabetes mellitus (DM) has emerged as a significant global concern that accounts for nearly 90% of type 2 DM cases worldwide and characterized by insulin resistance. Hyperglycemia in diabetes leads to increased fibrinogen levels and activates the coagulation cascade, thereby triggering atherothrombotic events. Aim and Objective: The study was designed to evaluate the coagulation profile (activated partial thromboplastin time, prothrombin time, and INR) in type 2 diabetes and to analyze the correlation between glycated hemoglobin (A1C) and coagulation profile among the OPD patients coming to AIIMS Patna. Methods: A total of 234 patients were included in the study who were divided into 3 categories based on their glycemic status. 85 were non-diabetic, 65 were pre-diabetic, and 84 were diabetic. The demographic profile and clinical details were recorded. Fasting blood glucose, glycated hemoglobin, coagulation parameters such as prothrombin time, INR, and activated partial thromboplastin time along with other biochemical parameters were investigated. Results: There was a statistically significant association found between the coagulation profile and the two groups (Diabetics and Non-diabetics). The present study also found significant correlations between age and the diabetic group as compared to the non-diabetic group. A strong statistical significance was found between the gender and coagulation profile PT/INR. A statistically significant difference was found in the pre-diabetic and diabetic groups for coagulation parameters such as the activated partial thromboplastin time and prothrombin time (APTT and PT). Conclusion: Clinical tests for prothrombin time, INR, and activated partial thromboplastin time are relatively inexpensive and readily available. The present study shows that a significant association was found between prothrombin time and activated partial thromboplastin time with the glycemic status among the diabetic as compared to non-diabetic or pre-diabetics. These findings can be used as important hemostatic markers in diabetic patients, especially in those at high risk for thrombotic complications.